Measurement of yCP in D0–D¯0 oscillation using quantum correlations in e+e−→D0D¯0 at s=3.773 GeV - M. Ablikim; M.N. Achasov; X.C. Ai; O. Albayrak; M. Albrecht; D.J. Ambrose; A. Amoroso; F.F. An; Q. An; J.Z. Bai; R. Baldini Ferroli; Y. Ban; et al. (Physics Letters B, 2015)
We report a measurement of the parameter yCP in D0–D¯0 oscillations performed by taking advantage of quantum coherence between pairs of D0D¯0 mesons produced in e+e− annihilations near threshold. In this work, doubly-tagged D0D¯0 events, where one D decays to a CP eigenstate and the other D decays in a semileptonic mode, are reconstructed using a data sample of 2.92 fb−1 collected with the BESIII detector at the center-of-mass energy of s=3.773 GeV. We obtain yCP=(−2.0±1.3±0.7)%, where the first uncertainty is statistical and the second is systematic. This result is compatible with the current world average. Keywords: BESIII, D0–D¯0 oscillation, yCP, Quantum correlation